Public Perception on the Existence of Macaca hecki and Macaca tonkeana in Protected Forest and Pangi Binangga Nature Reserve of Central Sulawesi - Manap Trianto; Nur Herjayanti; Moh Dahri Kisman; Efendi Efendi; Sandi Fransisco Pratama; Herlangga Adiputra; Sri Hardianti; Agung Dwi Kurniawan (Jurnal Biologi Tropis, 2021)
Wildlife is one of the biological natural resources that can be use it sustainably and sustainably, because wildlife is a natural resource renewable or renewable biological (renewable resources). This study aims to determine public perception of the exixtence of Macaca hecki and Macaca tonkeana in Protected Forest and Pangi Binangga Nature Reserve of Central Sulawesi. This research was carried out along the Palu-Parigi trans road which is in the Protected Forest and Pangi Binangga Nature Reserve, Central Sulawesi Province in April - June 2021. The results showed that presence of endemic Sulawesi macaque (M. hecki and M. tonkeana) along the Palu-Parigi trans road which is in the Protected Forest and Pangi Binangga Nature Reserve area causes various problems such as people experiencing unpleasant events with the presence of macaque, stolen goods, enter into community plantations, and damage various types of agricultural crops (avocado, cloves, cocoa, and several other fruits).